Implementasi Religious Culture dalam Mengatasi Degradasi Akhlak Siswa di SMK Negeri 2 Probolinggo - Fatin, Asy’ad Asy’ari; Khoiriyah, Khoiriyah (Lembaga Yasin AlSys, 2024)
The decline in students' morality in the modern era has become a pressing concern, particularly in the field of education. One potential approach to addressing this issue is through the implementation of a religious culture. This study seeks to examine how religious culture is applied to mitigate the decline in students' morals at SMK Negeri 2 Probolinggo. This research employs a qualitative descriptive method, gathering data through interviews, observations, and document analysis. The results indicate that implementing religious culture at SMK Negeri 2 Probolinggo is part of the school’s strategic efforts. These efforts include activities such as congregational prayers, religious study sessions, spiritual development programs, and the integration of religious values into academic subjects and extracurricular activities. Furthermore, the school’s supportive environment, which promotes religious practices and adherence to moral norms, significantly contributes to shaping students' character. In conclusion, the adoption of religious culture has demonstrated a positive influence in enhancing students' moral conduct and reinforcing their sense of social responsibility.